The world species of Balcha Walker (Hymenoptera: Chalcidoidea: Eupelmidae), parasitoids of wood-boring beetles - Gibson, Gary A.p. (Zootaxa, 2005)
The world species of Balcha Walker (Hymenoptera: Eupelmidae) are revised, keyed and illustrated. Sixteen species are recognized, including two that are newly classified in the genus, B. reticulata(Nikol’skaya) n. comb. and B. splendida (Girault) n. comb., and eight that are described as new, B. camptogastra n. sp., B. dictyota n. sp., B. enoptra n. sp., B. eximiassita n. sp., B. laciniosa n. sp., B. punctiscutum n. sp., B. reburra n. sp., and B. reticulifrons n. sp. Evidence for the monophyly of Balcha is discussed and the 16 species are segregated into four species groups based on morphological features. Balcha indica (Mani & Kaul) is newly recorded from the eastern United States (Maryland, Michigan, Virginia) as an accidental introduction from the Oriental region and as an adventitious parasitoid of the emerald ash borer, Agrilus planipennis Fairmaire (Coleoptera: Buprestidae).